Marcas de interatividade em produções textuais de estudantes da rede pública de ensino no fundamental II - Trajano, Cassandra de Lemos (2012)
Assuming that, linked to social practices and not just the teaching goals, teaching the language promotes interaction, integration and social inclusion, this work presents an investigation into the operation sociocomunicative and discursive marks of interactivity in textual productions of students in 9th grade of basic education, the municipal school of two schools in the metropolitan area of Recife. Is concerned with describing and analyzing data that contribute to stress the importance of the educational work with the genres of texts written textual productions, proposes that the text genres assume specific characteristics to adapt to different situations of real use, making it a production of socially situated language. The research, which general aims investigate if there are more marks of interactivity in textual productions than in school writings, works with the hypothetical-deductive method consists of content analysis (textual productions) in addition to the bibliography resource and on the assumption that the use of the trademarks with interactive textual genres is one of the merits of working with discursive genres. Thus, surveying the textual productions of the students, investigating the marks of interactivity in these productions , perform comparative analysis between textual productions and write school , investigate the practices of teaching and the influence of orality in write, considering the typological continuum between these two arrangements , are as specific objectives of this work .The corpus of 19 texts analyzed, in which, mostly manifested itself in an interactive relationship between the interlocutors . Supporting on theoretical and methodological principles arising from sociodiscursive interactionism and the principle of dialogism , this investigation worked his way under a methodological approach that involves the textual productions as main object of teaching with the text as the focus of work.From the results obtained, conclusions are taken off: 1. more than simple strategies of textualization, the interactivity marks represent a important aspect of the interaction reading/writer and language 2. the working with interactivity marks in the genres encourages the review of obsolete positions on the speech -writing continuum to organize production of the text